Karakteristik Kimia dan Organoleptik Nugget Ikan Tenggiri dengan Penambahan Tepung Daun Kelor - Booy, Zikrila M; Augustyn, Gelora H; Moniharapon, Erynola (Tropical Small Island Agriculture Management, 2023)
This study aims to determine the chemical and organoleptic characteristics of mackerel fish nuggets with the addition of Moringa lea flour. This study was designed using a completely randomized design with the addition of Moringa leaf flour consisting of 4 treatment levels, namely 0%, 5%, 10%, and 15% with 3 replications. Observation was made on the analysis of the chemical properties of fish nuggets with the addition of Moringa leaf flour, namely ash content, water content, fat content, protein content, and carbohydrate content. Followed by organoleptic testing, organoleptic testing was carried out using hedonic tests and hedonic quality which included color, aroma, taste, and texture. The treatment with the addition of 5% concentration of Moringa leaf flour on mackerel fish nuggets is the best treatment with chemical characteristics, namely the chemical characteristics of mackerel fish nuggets with the addition of Moringa leaf flour, namely ash content of 3,22%, water content 59,30%, fat content 1,61%, protein content 20,71% and carbohydrate content 15,14%. While the hedonic organoleptic characteristics of color 2,15 (like), aroma 2,05 (slightly like), taste 2,35 (slightly like), texture 2,3 (somewhat like). The hedonic quality is color 2 (slightly green), aroma 1,7 (no sceny of moringa), taste 1,95 (no taste of moringa), texture 2 (slightly chewy).